2020
DOI: 10.1037/ccp0000462
|View full text |Cite
|
Sign up to set email alerts
|

Predicting treatment failure in regular care Internet-Delivered Cognitive Behavior Therapy for depression and anxiety using only weekly symptom measures.

Abstract: To my family Josefin, Selma and Oskar. Not only did they put up with me during the entire PhD journey, but they also spent the last two weeks of it in quarantine with me because of the coronavirus pandemic of 2020.ABSTRACT Background: Internet-delivered Cognitive Behavior Therapy (ICBT) is efficacious for a number of psychiatric disorders and can be successfully implemented in routine psychiatric care. Still, only about half of patients experience a good enough treatment outcome. Using data from the early p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 120 publications
2
30
0
Order By: Relevance
“…et al 2015b) and an individually tailored intervention with an insomnia component (Kraepelien et al 2019). In a previous study by our group, we used data during the first treatment weeks, including insomnia symptom scores, depression scores and ratings of knowledge gain and homework quantity and quality, to make individual predictions of the success (treatment response or remission) of the participants' treatment (Forsell et al 2019a). The study showed that prediction during treatment can be successfully used in an adaptive treatment strategy, i.e.…”
mentioning
confidence: 99%
“…et al 2015b) and an individually tailored intervention with an insomnia component (Kraepelien et al 2019). In a previous study by our group, we used data during the first treatment weeks, including insomnia symptom scores, depression scores and ratings of knowledge gain and homework quantity and quality, to make individual predictions of the success (treatment response or remission) of the participants' treatment (Forsell et al 2019a). The study showed that prediction during treatment can be successfully used in an adaptive treatment strategy, i.e.…”
mentioning
confidence: 99%
“…However, reports on behavioral treatment outcome predictors are contradictory, and the reported effects are usually small. Forsell et al (2020) reported on 4310 patients treated for depression, panic disorder, or social anxiety disorder with the Internetdelivered CBT and found that patients not responding to CBT can be predicted with about 70% accuracy. However, this accuracy rate was only achievable half way through the treatment (week 6 of 12), and pre-treatment subjective symptom severity ratings did not significantly predict post-treatment outcomes (Forsell et al, 2020).…”
Section: Identifying Prognostic Markers Of Cbt Outcomementioning
confidence: 99%
“…Forsell et al (2020) reported on 4310 patients treated for depression, panic disorder, or social anxiety disorder with the Internetdelivered CBT and found that patients not responding to CBT can be predicted with about 70% accuracy. However, this accuracy rate was only achievable half way through the treatment (week 6 of 12), and pre-treatment subjective symptom severity ratings did not significantly predict post-treatment outcomes (Forsell et al, 2020). In a similar way, Hilbert et al (2020) predicted CBT outcome in a naturalistic sample from a university-based outpatient center with 2147 patients who received face-to-face CBT.…”
Section: Identifying Prognostic Markers Of Cbt Outcomementioning
confidence: 99%
“…by matching patients to the treatment option most likely to be beneficial, or use an adaptive treatment strategy to predict the risk of treatment failure early in treatment and adjust the treatment for those with a high risk (Forsell, Jernelöv, et al., 2019). A strong, and often pragmatically available, predictor of future symptom levels, are previous symptoms measured in the same way (Forsell, Isacsson, et al., 2019; Schibbye et al., 2014). However, it is likely that additional predictors need to be weighed in, in order for a prediction model to be optimised and clinically useful.…”
Section: Introductionmentioning
confidence: 99%